Haematological studies in pregnant Beetal x Assam local goat - BHATTACHARYYA, H K; GOSWAMI, B K; CHAKRAVARTY, P; BISWAS, R K (The Indian Journal of Animal Reproduction, 2023)
Different haematological constituents were studied in twenty impregnated crossbred (Beetal x Assam oc l) goats. The packed cell volume, number of erythrocytes and different leucocytic count did not differ s1gnificantly. However, the overall mean values were found to be reduced significantly during early pregnancy for haemogobin content (P<0.0 l) and leucocytic count (P<0.05).